THU0016 A comprehensive contribution of genes of the hypoxia inducible factor-1 alpha signaling pathway to knee osteoarthritis susceptibility. (15th June 2017) - Fernandez-Torres, J; Martínez-Nava, GA; Lόpez-Reyes, A; Zamudio-Cuevas, Y; Clavijo-Cornejo, D; Martínez-Flores, K; Gutiérrez-Ruíz, MC; Gόmez-Quiroz, LE; Pineda, C
Abstract : Background: The hallmark of osteoarthritis (OA) is the breakdown of articular cartilage. Articular cartilage is an avascular tissue, and this generates a hypoxic microenvironment. Hypoxia inducible factor-1α (HIF-1α) is the main transcriptional regulator of cellular and developmental response to hypoxia. Objectives: The present study was designed to investigate whether genetic polymorphisms of the HIF-1α signaling pathway are involved in the development of knee OA. Methods: A total of 243 unrelated Mexican-mestizo individuals comprising 93 knee OA patients and 150 healthy controls were recruited into the study. 42 genetic polymorphisms from 22 genes involved in the HIF-1α signaling pathway ( PIK3R1, AKT2, GSK3B, IL6, AGER, HIF1A, EGLN1, VHL, HIF1AN, VEGFA, EPO, NOS2, NOS3, IGF1, EGF, EDN1, MMP1, MMP3, MMP13, CA, COL2A1, COL3A1 ) were genotyped in cases and controls using TaqMan-based allelic discrimination assays. Results: After adjusting for age, sex and admixture, significant associations with knee OA were found for 7 SNPs in the case-control study. The following genotypes and alleles were associated with protection against OA: the CT genotype of the HIF1AN rs11190613 polymorphism (OR=0.44, 95% CI=0.19–1.0, P =0.05); the AA genotype of the VEGFA rs1570360 polymorphism (OR=0.14, 95% CI=0.02–0.69, P =0.016); the GT genotype and T allele of the VEGFA rs729761 polymorphism (OR=0.47, 95% CI=0.22–1.0, P =0.05; and OR=0.51, 95% CI=0.27–0.97, P =0.041, respectively); the GA genotype of the COL2A1 rs1793953 polymorphism (OR=0.40, 95% CI=0.20–0.79, P =0.008); and the GG genotype and G allele of the CKM rs4884 polymorphism (OR=0.34, 95% CI=0.14–0.84, P =0.019; and OR=0.51, 95% CI=0.32–0.82, respectively). Otherwise, the CT genotype of the COL3A1 rs2138533 polymorphism (OR=2.89, 95% CI=1.28–6.5, P =0.01); and the GA genotype of the IGF1 rs35767 polymorphism (OR=2.22, 95% CI=1.11–4.43, P =0.024) were associated with an increased risk of OA. However, by using of epistatic interactions between HIF-1α pathway polymorphisms, we found that the gene-gene interaction had a synergistic effect over the estimated OR-values (see table). Conclusions: In this study we could observe that the gene-gene interaction of the HIF-1α signaling pathway highly increases the risk of developing OA, with the exception of COL2A1 and HIF1AN interaction which had a protective role against OA. Further studies are needed to validate this results. References: Fernández-Torres J, et al. Polymorphic variation of hypoxia inducible factor-1 A (HIF1A) gene might contribute to the development of knee osteoarthritis: a pilot study. BMC Musculoskelet Disord 2015; 16:218. Rodríguez-Fontanela C, et al. Assessment of osteoarthritis candidate genes in a meta-analysis of nine genome-wide association studies. Arthritis Rheumatol 2014; 66:940–949. Disclosure of Interest: None declared